2019
DOI: 10.1016/j.physa.2019.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Momentum and contrarian effects on the cryptocurrency market

Abstract: Working Papers contain preliminary research results. Please consider this when citing the paper. Please contact the authors to give comments or to obtain revised version. Any mistakes and the views expressed herein are solely those of the authors M Mo om me en nt tu um m a an nd d c co on nt tr ra ar ri ia an n e ef ff fe ec ct ts s o on n t th he e c cr ry yp pt to oc cu ur rr re en nc cy y m ma ar rk ke et t K Kr rz zy ys sz zt to of f K Ko oś ść ć* *, , P Pa aw we eł ł S Sa ak ko ow ws sk ki i, , R Ro ob be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…The emergence of Bitcoin and other cryptocurrencies in the market has been studied during this decade (Gil-Alana et al, 2020). The literature on cryptocurrencies has covered a wide range of divergent aspects, beginning with the technical and investment characteristics of Bitcoin in relation to risk and returns (Wei, 2018;Tan et al, 2020;Omane-Adjepong et al, 2019;Kosc et al, 2019;Da Gama Silva et al, 2019;Brauneis and Mestel, 2018;Bouri, et al, 2019;Antonakakis et al, 2019;Yi et al, 2018;Koutmos, 2018). There are vast sum of studies focusing on Bitcoin suitability as an asset to diversify the risks of other traditional assets, which is consistent with the purpose of this paper.…”
Section: Literature Reviewsupporting
confidence: 60%
“…The emergence of Bitcoin and other cryptocurrencies in the market has been studied during this decade (Gil-Alana et al, 2020). The literature on cryptocurrencies has covered a wide range of divergent aspects, beginning with the technical and investment characteristics of Bitcoin in relation to risk and returns (Wei, 2018;Tan et al, 2020;Omane-Adjepong et al, 2019;Kosc et al, 2019;Da Gama Silva et al, 2019;Brauneis and Mestel, 2018;Bouri, et al, 2019;Antonakakis et al, 2019;Yi et al, 2018;Koutmos, 2018). There are vast sum of studies focusing on Bitcoin suitability as an asset to diversify the risks of other traditional assets, which is consistent with the purpose of this paper.…”
Section: Literature Reviewsupporting
confidence: 60%
“…Qing et al (2019) using DFA and MF-DFA analysis found a strong momentum effect in BTC and ETH price behavior, and a reversion effect in XRP and EOS prices after abnormal returns. Kosc et al (2019) investigated investment strategies in the cryptocurrency market and reported a clear and significant dominance of the short-term contrarian effect over momentum effect. Panagiotis et al (2019) identified momentum effects in the cryptocurrency market; these are highly significant for short-term portfolios but less so in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Cheung et al 2015;Aalborg et al 2019;. A number of recent studies analyze momentum and contrarian effects in this market Kosc et al 2019;Panagiotis et al 2019;Qing et al 2019;Yukun and Tsyvinski 2019) and obtain mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the efficiency of tested strategies we calculate the following performance metrics based on Kosc et al (2019) [45] and Bui and Ślepaczuk (2021) [46].…”
Section: Performance Metricsmentioning
confidence: 99%